The "speed gene" effect of myostatin arises in Thoroughbred horses due to a promoter proximal SINE insertion. - Mary F Rooney; Emmeline W Hill; Vincent P Kelly; Richard K Porter (PLoS ONE, 2018)
Thoroughbred horses are finely-tuned athletes with a high aerobic capacity relative to skeletal muscle mass, attributable to centuries of genetic selection for speed and stamina. Polymorphisms in the myostatin gene (MSTN), a pronounced inhibitor of skeletal muscle growth, have been shown to almost singularly account for gene-based race distance aptitude in racehorses. In Thoroughbreds, two MSTN polymorphisms, a single nucleotide variation in the first intron (SNP g.66493737C>T) and a non-coding transposable element within the promoter region (a 227 bp SINE insertion) are of particular interest. Until now, it has not been clear which of these variants affect skeletal muscle phenotypes or whether both can impact racing performance. In a large cohort of Thoroughbreds, we observed a complete concordance between the SNP and the SINE insertion. By means of in vitro assays in C2C12 myoblasts, we isolated the SNP variant from the SINE polymorphism and showed the latter is exclusively responsible for adversely affecting transcription initiation and gene expression thereby limiting myostatin protein production. Mapping the MSTN transcription start site in horse skeletal muscle likewise revealed anomalous transcription initiation in the presence of the SINE insertion. Our data provides mechanistic evidence that the SINE insertion uniquely accounts for the MSTN "speed gene" effect on race distance aptitude in the Thoroughbred horse.